ANALISIS KINERJA PADA PROYEK PERBAIKAN KAPAL TUNDAMENGGUNAKAN METODE EARNED VALUE ANALYSIS - Ikhsaniyah Putri Mulyono; Fitri Hardiyanti; Aditya Maharani (Proceeding Maritime Business Management Conference, 2023)
One of the shipyards in Madura is currently executing the tug boat Transko Gagak repair project. This project has experienced an 11-day delay due to several obstacles, including a leakage issue with the floating dock pump, resulting in a failed docking attempt, as well as delays in the procurement process. The purpose of this study is to analyze the performance of the ship repair project in terms of cost and time. The methods employed for analyzing thisproject's performance are Earned Value Analysis (EVA). The analysis results on the 22nd day indicate that the project's schedule performance is 0.59 (SPI < 1), indicating a delay of 38.93% from the initial planned project completion of 100%, with actual completion of 61.07% of the work. In terms of cost performance, the value is 1.47 (CPI > 1), signifying thatthe expenditures have been lower than the initial budget plan. This reduction is due to the elimination of certain work items during the project execution.